Validation test for development of six months old numerical child dummy model - Mohamad Sulaiman, Ibrahim; Rakhmad Arief, Siregar; Abdul Hamid, Adom, Dr.; Shah Fener Khan (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.